Resuscitation of general paediatrics in the UK. Issue 12 (21st November 2006) - Wacogne, I; Scott-Jupp, R; Chambers, T
Abstract : "The report of my death was an exaggeration", said Mark Twain. For a dying specialty, general paediatrics has certainly been looking very healthy recently. It is timely to examine why our specialty was thought to be at such risk, and to explore why, although in many cases shocked and confused, it is well on the way to recovery. This article explores what is needed to keep it healthy to ensure that the general paediatrician is at the centre of the delivery of paediatrics in the UK.